Nucleic acid amplification techniques for the detection of Schistosoma mansoni infection in humans and the intermediate snail host: a structured review and meta-analysis of diagnostic accuracy. (November 2021) - Li, Hong-Mei; Qin, Zhi-Qiang; Bergquist, Robert; Qian, Men-Bao; Xia, Shang; Lv, Shan; Xiao, Ning; Utzinger, Jurg; Zhou, Xiao-Nong
Highlights: This study evaluated nucleic acid amplification techniques for diagnosing Schistosoma mansoni infections Pooled sensitivity was 89.79% and specificity was 87.70% for human samples qPCR showed modest sensitivity (68.75%) and high specificity (92.45%) for rodents PCR and nPCR assays showed sensitivity of 90.06% and specificity of 85.51% for snails Abstract: Background: Schistosomiasis is a parasitic disease caused by hematodes of genus Schistosoma . This review evaluated the available nucleic acid amplification techniques for diagnosing S. mansoni infections in humans, intermediate host snails, and presumed rodent reservoirs. Methods: Sensitivity, specificity, diagnostic odds ratio (DOR), and 95% CI were calculated based on available literature. The potential of PCR, nPCR, PCR-ELISA, qPCR, and LAMP was compared for diagnosing S. mansoni infections. Results: A total of 546 published records were identified. Quality assessment by QUADAS-2 revealed an uncertain risk in most studies, and 21 references were included in the final. For human samples, the four nucleic acid amplification techniques showed an overall sensitivity of 89.79% (95% CI: 83.92%-93.67%), specificity of 87.70% (95% CI: 72.60%-95.05%), and DOR of 37.73 (95% CI: 21.79-65.33). LAMP showed the highest sensitivity, followed by PCR-ELISA, PCR, and qPCR, while this order was almost reversed for specificity; qPCR had the highest AUC. For rodent samples, qPCR showed modest sensitivity (68.75%, 95% CI: 43.32%-86.36%) and high specificity (92.45%, 95% CI: 19.94%-99.83%). For snail samples, PCR and nPCR assays showed high sensitivity of 90.06% (95% CI: 84.39%-93.82%) and specificity of 85.51% (95% CI: 54.39%-96.69%). Conclusion: Nucleic acid amplification techniques had high diagnostic potential for identifying S. mansoni infections in humans.